Is trust in information sources associated with drug use? - Gabrovec, Branko (Zdravstveno varstvo, 2023)
Aim: Communication and information sources can play an important role when addressing drug use. The aim of this study is to assess the association of different levels of trust in information sources regarding drug use within different population groups. Methods: Data was gathered using a mixed methods approach, with an online survey and interviews. A structured questionnaire was designed for data collection using the methodology of the European Monitoring Centre for Drugs and Drug Addiction, with additional items measuring trust in the information sources. Results: In total 9,161 inhabitants of Slovenia aged 15-64 years and living in the private households completed the survey as part of this non-experimental quantitative study (response rate: 57%). A total of 20.7% of the participants reported having used cannabis or hashish at least once in their lives, 2.5% cocaine/crack cocaine and 0.4% heroin. Mean age of the first cannabis/hashish use was 19.59 years, cocaine/crack cocaine 22.73 years and heroin 20.63 years. The participants most value and trust the information sources regarding tobacco, alcohol and illicit drugs if it comes from healthcare workers or immediate family and other relatives, and put the least trust in the internet and television. Conclusions: The data show that drug users have less trust in the given information sources compared to the whole sample. The present research serves as evidence for development and implementation of targeted interventions, including communication activities and tools.
Keywords: drug use; information sources; interviews; intervjuji; online surveys; spletne raziskave; trust; uporaba drog; viri informacij; zaupanje